STRUCTURAL AND SPATIAL CHANGES IN AGRICULTURE - Mesquita, Fernando; Furtado, André Tosi (Mercator, 2019)
From a region where until the end of XIX century the cattle was the only profitable production, the South of the State of Goiás became one of the cores of Brazilian agribusiness. Besides the cattle, the region also stands out in the production of soybean, corn, sugarcane, and poultry. This change involved different process of regional and urban organization. Using the South of Goiás case, this paper aims to comprehend how structural and spatial changes were combined in the transformation of a late region in a dynamic agricultural region. To study this process, the structural changes of this region were divided into four phases. The spatial changes were thought according to four possibilities based on fragmentation and integration forces. The idea is to combine both structural and spatial changes to define the historical trajectory of urban and regional growth in the South of Goiás.     Keywords : Agribusiness; Structural Changes; Spatial Changes; South of Goiás.